Hubungan Lingkungan Belajar dengan Hasil Belajar Seni Rupa Kelas VIII di SMPN 43 Padang - Fajri Alfallah; Yofita Sandra (Departement of Mathematics Education, 2023)
Abstract The purpose of this study was to test how much the learning environment relates to the learning outcomes of class VIII fine arts at SMPN 43 Padang. This type of research is quantitative research with descriptive methods. The population of this study was class VIII students of SMP Negeri 43 Padang. The sampling technique in this study was proportional random sampling, which was 69 people. The bound variable in this study is the results of learning fine arts class VIII. The independent variable in this study is the learning environment. The instrument in this study used a questionnaire. Data analysis techniques in this study used correlation and regression techniques. Based on the results of the research and discussion above, it can be concluded that the learning environment has a significant relationship with the learning outcomes of class VIII students of SMP Negeri 43 Padang. This is evidenced by the results of the t test, which is a calculation greater than the ttabel, which is 2.56 > 1.67. Based on the results of the questionnaire, the family environment of the students of SMP Negeri 43 Padang is very good. Parents instill learning discipline, provide attention and supervision. The family's relationships, facilities, and economic conditions are also very good. In the school environment, the relationship between students and students and teachers is very good. In addition, learning methods and school facilities are also very adequate. In the community, students play an active role and enjoy doing activities in the community and are beneficial to activities at school. In addition, the environment where students live likes to work together and likes to have consensus if they make decisions regarding the community. The neighborhood where he lives helps each other when there are neighbors who are struggling.